Sintesis Silikon dari Silika (SiO2) Menggunakan Metode Reduksi Hidrotermal - Azzahra, Wenalda Hanifah; Beri, Deski; Aini, Syamsi; Parbuntari, Hesty (Periodic, 2024)
Silicon is one of the materials whose utilization is getting bigger along with the times. Hydrothermal reduction method is one of the methods that can be done to synthesize silicon from natural materials because silicon does not exist freely in nature. The purpose of this research is to synthesize silicon using hydrothermal reduction method. The precursor used in the reduction process is silica (SiO2). The metal used as a reductant is magnesium metal and the molten salt that can be used is AlCl3. The reduction process is carried out by varying the reduction temperature to see the degree of crystallinity of silicon formed. Silicon formed is seen at the peak of  28.44, 47.30, 56.11, 69.13 dan 76.38.